A synthesis of expatriate competence, intelligence, adaptability, work-role demand and organisational support on expatriation effectiveness. (26th December 2019) - Lee, Li-Yueh; Nguyen, Phuoc-Thien
Based on a series of literature reviews, 27 research hypotheses were developed for further empirical testing. Using 244 overseas expatriate respondents as the sample, the research results show that cross-cultural static competences have positive influence on cross-cultural dynamic competences and cross-cultural adjustment; work role demands have a negative influence on cross-cultural dynamic competences and cross-cultural adjustment; relational skills. Perceived host attitude toward expatriates has a positive influence on expatriate adjustment; cross-cultural dynamic competences have positive influence on cross-cultural adjustment; cross-cultural dynamic competences and adjustment have a positive influence on expatriate effectiveness; and innovative work behaviour and job satisfaction have a positive influence on expatriate performance. In terms of moderating effects, expatriate intelligence and cultural adaptability strengthen the influence of cross-cultural static competences and work role demands on cross-cultural dynamic competences and adjustment; also, perceived assignment value and organisational support strengthen the influence of cross-cultural dynamic competencies and adjustment on expatriate effectiveness.